1988
DOI: 10.1159/000124900
|View full text |Cite
|
Sign up to set email alerts
|

Antiglucocorticoid RU 38486 Attenuates Retention of a Behaviour and Disinhibits the Hypothalamic-Pituitary Adrenal Axis at Different Brain Sites

Abstract: Adrenalectomized rats displayed a deficiency in retention of an immobility response acquired during an initial 15-min forced swimming procedure (Porsolt swimming test) and measured 24 h later in a 5-min retest session. The deficit could be restored dose dependently with the glucocorticoid dexamethasone (µg range) administered 15 min after the initial test. The antiglucocorticoid RU 38486 administered subcutaneously (1 and 10 mg/kg) inhibited the dexamethasone effect and caused a parallel shift in the dose-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
117
3
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(129 citation statements)
references
References 31 publications
8
117
3
1
Order By: Relevance
“…Jefferys and colleagues (Jefferys et al, 1983;Jefferys and Funder, 1987) were the first to show that the presence of glucocorticoids and opioid peptides after the initial test is necessary for the retention of the acquired immobility response in the retest. This finding was confirmed by De Kloet et al (1988) who have shown that local administration of the glucocorticoid receptor antagonist, RU38486, into the dentate gyrus of the hippocampus directly after the initial test disrupted this retention. Recently, however, it has been shown that inhibition of the synthesis of corticosterone with metyrapone reduced the immobility time during both initial test and retest (Bfiez and Volosin, 1994).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Jefferys and colleagues (Jefferys et al, 1983;Jefferys and Funder, 1987) were the first to show that the presence of glucocorticoids and opioid peptides after the initial test is necessary for the retention of the acquired immobility response in the retest. This finding was confirmed by De Kloet et al (1988) who have shown that local administration of the glucocorticoid receptor antagonist, RU38486, into the dentate gyrus of the hippocampus directly after the initial test disrupted this retention. Recently, however, it has been shown that inhibition of the synthesis of corticosterone with metyrapone reduced the immobility time during both initial test and retest (Bfiez and Volosin, 1994).…”
Section: Introductionmentioning
confidence: 52%
“…Low circulating levels of corticosterone predominantly occupy mineralocorticoid receptors, whereas after stress and during the circadian peak both mineralocorticoid receptors and gluco-corticoid receptors are activated (Reul et al, 1987). Behavioural effects of the synthetic glucocorticoid receptor antagonist and the mineralocorticoid receptor antagonist have been measured in animal models designed to examine anxiety (Korte et al, 1995), learning and memory (De Kloet et al, 1988;Jefferys et al, 1983;Jefferys and Funder, 1987;Oitzl and De Kloet, 1992;Oitzl et al, 1994) and learned helplessness (Papolos et ai., 1993). One of the behaviours sensitive to corticosterone (the principle glucocorticoid in the rat) is immobility in the Porsolt forced swim test.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal steroids play an important role in regulating both learned and unlearned fear and anxiety (Korte 2001;Calvo et al, 1998;Calvo and Volosin, 2001) and alterations in the balance between Type I or mineralocorticoid receptors (MR) and Type II or glucocorticoid receptors (GR) in the brain appear to play a role in these behaviors as well as in the etiology of depression and anxiety (de Kloet et al, 1988;Korte, 2001). MR and GR are expressed throughout the central nervous system, with GR showing a more widespread distribution and MR showing a discrete localization, such as in neurons of the hippocampus, regions of the amygdala, and brain stem (Ahima and Harlan, 1990;Ahima et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…MR and GR mediate different aspects of corticosterone (CS) action: for example, hippocampal MR is responsible for the maintenance of stability in the stress response system throughout the circadian cycle (Ratka et al, 1989;Dallman et al, 1992), whereas GR facilitates the recovery of the system after the exposure to a stressful stimulus (de Kloet et al, 1988). Moreover, the activation of MR in neurons from the hippocampal CA1 region stabilizes local excitability while it is reduced by GR activation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation